2009
DOI: 10.1631/jzus.b0820372
|View full text |Cite
|
Sign up to set email alerts
|

Institutional experience of PTH evaluation on fine-needle washing after aspiration biopsy to locate hyperfunctioning parathyroid tissue

Abstract: Assaying parathyroid hormone (PTH) in the washing liquid after fine-needle aspiration biopsy (FNAB) seems to be a valid approach to locate parathyroid tissue. PTH-FNAB was evaluated in 47 patients with a clinical picture of primary hyperparathyroidism (PHP) and ultrasonography (US) suggestive of parathyroid lesion. The patients were subdivided into two groups on the basis of the absence or presence of US thyroid alterations. The result of PTH-FNAB was compared with those of cytology, scintigraphy and, in 24 pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
38
0
8

Year Published

2012
2012
2021
2021

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 36 publications
(50 citation statements)
references
References 22 publications
4
38
0
8
Order By: Relevance
“…In the presented study, the routine FNAB allowed us to diagnose parathyroid tissue in 30% of cases. That value is similar to data reported by Bancos et al [20] -31% -and is higher than that showed by Giusti et al [8] -17%. The relatively high percentage of non-diagnostic Comparison of the thyroid size, the size of focal lesion suggestive of pathological parathyroid, and …”
Section: Discussionsupporting
confidence: 91%
See 4 more Smart Citations
“…In the presented study, the routine FNAB allowed us to diagnose parathyroid tissue in 30% of cases. That value is similar to data reported by Bancos et al [20] -31% -and is higher than that showed by Giusti et al [8] -17%. The relatively high percentage of non-diagnostic Comparison of the thyroid size, the size of focal lesion suggestive of pathological parathyroid, and …”
Section: Discussionsupporting
confidence: 91%
“…However, in all the cases, we observed PTH-FNAB concentrations to be either higher than serum PTH concentrations (frequently elevated into the hundreds or thousands of pg/mL) or very low if not undetectable, doubtlessly negative. Similarly, other reports have indicated that PTH level in the aspirate is rarely equivocal [6,[8][9]24]. Blood contamination in biopsies of non-parathyroid lesions may explain the small amounts of PTH detected in negative aspirates [15].…”
Section: Prace Oryginalnementioning
confidence: 86%
See 3 more Smart Citations